Effect of growth hormone administration on ameliorating pregnancy outcome in women with advanced maternal age and exploration of its optimized utilization - Feng, Qihui; Wang, Yanbin; Han, Hongjing; Shen, Huan (Frontiers in Endocrinology, 2023)
Background: Age-related fertility decay is a great challenge for clinicians. Growth hormone (GH) supplementation has been studied as an adjuvant since late 1980s. However, it has not come to a consensus on the GH administration due to the ambiguous efficacy among studies with different enrolled population and dosage regime.Methods: A self-controlled retrospective study was conducted on women with advanced maternal age who underwent at least a previous cycle without GH (GH-) and a subsequent cycle with GH cotreatment (GH﹢). The ovarian stimulation parameters and outcomes were compared between the two cycles and logistical analyses was applied to further explore the association between GH administration protocol as well as other clinical parameters and cumulative live birth in GH﹢cycle.Results: A total of 150 women aged 35-43 were included. The number of oocytes retrieved, MⅡ oocytes, 2PNs, transferrable embryos and good-quality embryos in GH﹢ significantly increased (p < 0.001). The proportion of cycles with no transferrable embryos was significantly reduced in GH﹢ cycle compared with previous GH-cycle (3 vs. 32; p < 0.001). GH co-treatment cycles showed significantly higher clinical pregnancy rates (43.75% vs. 6.06%；38.35% vs. 12.04%, p < 0.001), live birth rates (29.17% vs. 0 ; 27.07% vs. 0, p < 0.001) in both fresh and frozen-thawed embryo transfer cycle. Cumulative live birth rate of the GH﹢ cycle reached 33.33%. Use of GH prior to Gn stimulation and lasting until the hCG day seemed to achieve a higher successful live birth rate (OR 2.312, p=0.032).2 This is a provisional file, not the final typeset article Conclusions: GH supplementation could ameliorate pregnancy outcome in women with advanced maternal age. Dosage regimen of long-term pretreatment prior to Gn stimulation (4 IU every other day) and 4 IU per day until hCG day may of greater efficacy compared with concurrent administration with Gn. Additionally, it's worthy of exploring whether an individualized dosage regimen based on the IGF or IGFBP level of patient would be more reasonable and effective. More well-designed prospective trials with large sample size and fundamental experiments on the mechanism are required to testify findings above.